Effect of trifluoperazine on rabbit cortical collecting tubular response to vasopressin. - Dillingham, M A (1986)
Anuran membrane studies suggest that the calcium-binding protein calmodulin is necessary for arginine vasopressin (AVP) to exert a hydro-osmotic effect. We therefore examined the effect of trifluoperazine and N-(6-aminohexyl)-5-chloro-1-naphtholene sulphonamide (W-7), chemically dissimilar calmodulin inhibitors, on hydraulic conductivity (Lp) response to AVP in rabbit cortical collecting tubules perfused in vitro. Trifluoperazine but not W-7 increased basal Lp in rabbit cortical collecting tubules. When cortical collecting tubules were pre-treated with either trifluoperazine or W-7, the effect of AVP to increase Lp was significantly inhibited. To determine the site of this inhibition, Lp responses to exogenous cyclic adenosine 3',5'-phosphate (AMP) were studied. Both trifluoperazine and W-7 pretreatment significantly inhibited the effect of a cyclic AMP analogue to increase rabbit cortical collecting tubule Lp. These results suggest that calmodulin may be an important mediator of the hydro-osmotic response to AVP in the mammalian cortical collecting tube by acting at a site or sites distal to cyclic AMP formation.